2021
DOI: 10.1108/ijopm-09-2020-0660
|View full text |Cite
|
Sign up to set email alerts
|

Informal governance in the digital transformation

Abstract: PurposeThe purpose of this study is to explore if and how informal governance mechanisms are used for coordinating actors of digitalized supply networks.Design/methodology/approachA multiple case study analysis of ten German firms in digitalized supply networks is conducted. Data are collected through semi-structured expert interviews with interviewees having notable years of professional experience in purchasing or sales.FindingsThis research shows that reduced personal contacts in digitalized supply networks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(60 citation statements)
references
References 66 publications
5
55
0
Order By: Relevance
“…This accorded with Keller et al. ’s (2021) findings from German firms, which found that digitalization decreases the use of informal governance mechanisms, but also calls for further engagement regarding supply network disruption.…”
Section: Outcome Evaluation and Design Propositionssupporting
confidence: 80%
“…This accorded with Keller et al. ’s (2021) findings from German firms, which found that digitalization decreases the use of informal governance mechanisms, but also calls for further engagement regarding supply network disruption.…”
Section: Outcome Evaluation and Design Propositionssupporting
confidence: 80%
“…2.1 The relational exchange and signaling perspectives of norm of solidarity, blockchain, and trust Interorganizational relationship governance is pivotal to supply chain management (Cao and Lumineau, 2015). Rather than being a process or an activity, governance itself is a guidance framework for firms to behave in interorganizational relationships (Keller et al, 2021;Liu et al, 2009). Extant literature has pointed out the critical importance of governance mechanisms in achieving better relationship performance and satisfaction (e.g.…”
Section: Theoretical Foundationmentioning
confidence: 99%
“…Interestingly, the special issue is also characterized by the adoption of a variety of research methods, i.e. Delphi (Hohn and Durach, 2021), multiple case study (Keller et al, 2021;Aben et al, 2021) and survey (Yang et al, 2021;Paolucci et al, 2021;Faruquee et al, 2021;Son et al, 2021). This variety of methods highlights that research on governance in the context of digitalized supply chains is not exclusively at an exploratory stage; it seems research is advancing towards the development and testing of complex models to grasp the dynamics and implication of digital transformation in the context of buyer-supplier relationships.…”
Section: Main Themes Across the Articlesmentioning
confidence: 99%
“…The article sheds light on potential social sustainability issues that may be amplified as the results of AM adoption; moreover, implementing AM may also reinforce existing supply chain governance structures, currently dominated by powerful apparel retailers. Keller et al (2021) explore the role of informal governance mechanisms to coordinate actors of digitalized supply chains, using case studies of ten German firms. Digitalized supply chain may reduce the need for interpersonal contacts, which in turn may decrease the ability to coordinate with informal governance mechanisms; however, the need for personal contacts remains paramount in the context of specific phases of a digitalized business relationship; in other words, interpersonal contacts are not completely replaceable by digital technology.…”
Section: Articles Included In the Special Issuementioning
confidence: 99%
See 1 more Smart Citation